What the best college teachers do - Bain, Ken (Massachusetts: Harvard University Press, 2004)
Contents: What do they know about how we learn, how do they prepare to teach,what de they expect of their students,how do they conduct class,how do they treat their students,how do they evaluate their students and themselves,what can we learn from them.
Include appendix
Keywords: Profesores - Educación